Blockchain and the law : the rule of code - De Filippi, Primavera; Wright, Aaron (Writer on law) (Harvard University Press, 2018)
Blockchain technology enables the creation of decentralized currencies, decentralized applications powered by smart contracts, self-executing digital agreements, and intelligent assets that can be controlled over the Internet. Blockchains also enable the development of new governance systems with more democratic or participatory decision-making, and decentralized (autonomous) organizations that can operate over a network of computers without any human intervention. These applications have led many to compare the blockchain to the Internet, with accompanying predictions that this technology will shift the balance of power away from centralized authorities in the field of communications, business, and even politics or law. Blockchain and the Law explores the benefits and drawbacks of this emerging decentralized technology and argues that its widespread deployment will lead to expansion of what we term lex cryptographia: rules administered through self-executing smart contracts.- Resumé vydavatel
Keywords: blockchain (technologie); blockchain (technologie) -- právní aspekty; šifrování dat; blockchain (technology); blockchain (technology) -- legal aspects; data encryption; elektronické knihy; monografie; electronic books; monographs